“FORTALECIMIENTO TURÍSTICO AL PLAN DE DESARROLLO Y ORDENAMIENTO TERRITORIAL (PDOT), PARA LA PARROQUIA MALACATOS, CANTÓN Y PROVINCIA DE LOJA” - González Zhapa, Ashley Camila (2019)
The research "Tourism strengthening of the plan of development and territorial ordering (pdot), for the parish of Malacatos, canton and province of Loja" seeks to perfect the capacity of tourism management with the participation of the actors involved in tourism. The present research work has as a General Objective: the tourism strengthening to the plan of development and territorial ordering (PDOT), for the Parish Malacatos, canton and province of Loja, with three specific objectives: Make the diagnosis of the tourist component of the parish Malacatos , Canton and province of Loja. Prepare a tourism development proposal for the parish of Malacatos, cantón and Provincia de Loja through the application of a participatory methodology and design strategies for the application of the proposed proposal for tourism development for the parish of Malacatos, cantón and Provincia de Loja. To develop each of the objectives it was necessary to use some methodologies and techniques, for the first objective that consisted in the diagnosis of the parish Malacatos information was taken from a secondary source such as the PDyOT of the parish. In addition, the matrix of Carla Ricaurte which includes: general data of the study site, services, and infrastructure of basic services. The main tourist attractions were also determined through a participatory workshop to later elaborate the tourist inventory cards through direct observation, and the methodology of ranking tourist attractions of the Ministry of Tourism (MINTUR, 2017). Strengths, opportunities, weaknesses and threats through the SWOT matrix which was developed in conjunction with the local community in the validation of the diagnosis. For the second objective that consisted in the development of the tourism development proposal for the parish of Malacatos, cantón and Provincia de Loja through the application of a participatory methodology, it was worked on the basis of the matrix of strategies from which the development proposals arise. with its advantages and disadvantages to be later socialized to the community and selected according to their criteria. In the third objective, the application strategies for the proposed proposals were designed, thus defining the criteria under which each proposal should be developed. 5 Finally, the Malacatos parish has a good quality tourism infrastructure, infrastructure of basic services creating a tourist influx which can be evidenced in the registers of the establishments that provide the lodging service. There is little tourist signage in the parish, the lack of tourist information, the lack of promotion of tourist attractions, the lack of support from the external authorities to the GAD and the main entity in charge of the tourist activity MINTUR. With this project will contribute to the tourist and productive improvement of the community. In addition, it will contribute to the identification and positioning of Malacatos as a territory full of culture, tradition and an outstanding nature, productive and welcoming land. The recommendation for the Parish GAD is to consider the present tourist diagnosis for the update of the PDOT of the Parish. conduct training campaigns to the community on tourism. Participate in the external fairs of the Malacatos parish for further promotion. Implement an I-tur office to facilitate tourist information to visitors.